Information. No.5, After the World Conference of Action for Peace (article copy)
017a-0042-001 sent by Gillies Aug 25 July 25 AFTER THE WORLD CONFERENCE OF ACTION FOR PEACE The report of the World Conference of the International Peace Campaign in Information No. 4, indicated that certain very clear and concrete decisions were taken, and that the overwhelming majority of the delegations of all countries desired to see those decisions operated without loss of time. On the very day after the Conference, July 25th, the International Co-ordination Committee for Aid to Republican Spain, the Medical Centre (Centrale Sanitaire) and the International Children's Office invited the delegates of the various national co-ordinating bodies occupied with aid to Spain, to confer on the immediate practical steps to be taken in each country to give effect to the Conference decisions as far as Spain was concerned. The representatives of such national bodies in 18 countries were present, including M. Ayala, secretary of the National Committee of Aid in Spain itself, set up by decree of the Spanish government for the effectual distribution of all aid received. It was essentially a business meeting. Side by side with the actions to be carried out in the various countries, the perfecting of the machinery of co-ordination, national and international, was decided on. For example, each national co-ordination committee which had not already done so, is recommended to create a section of the Medical Centre and one of the Children's Office, to specialise on these branches of aid, full co-operation being ensured by meetings of the three secretaries. The Executive Committee of the International Co-ordination Committee was enlarged to include representatives of additional countries, and a representative of the young people's organisations which are doing such active work. The full executive is to meet every two months; and since it is impossible for the North American Committee to send one of its members to Europe so often, it has arranged with a resident in Europe, with whom it will keep permanent contact, to represent it. It was decided to organise in each country a national conference of aid to republican Spain on the lines of the great conference in England in April 1938. The Winter Campaign, for a special help during the cold weather, is to begin without delay, appeals to be made particularly for warm materials for clothing which will be made up by women refugees in the workshops of Republican Spain. In addition special campaigns of solidarity are to be carried out in commemoration of November 6th (anniversary of the glorious defence of Madrid) and during Christmas week. From "Informations" August 19, 1938. No. 5. 292/946/17a/42